The Influence Of Rahmatan Lil ‘Alamin Learner Profile On Students’ Religious Character - Sarianti, Opet; Remiswal, Remiswal; Marhamah, Marhamah; Sabri, Ahmad; Hidayati, Hidayati (Prodi Pendidikan Keagamaan Islam, 2025)
This research is motivated by the importance of strengthening the religious character of students in the madrasah environment. There are still students who have not prayed on time and are less active in religious activities such as commemorating Islamic holidays. Strategic efforts to strengthen religious character are carried out through the internalization of values in the Rahmatan Lil 'Alamin Student Profile (PPRA). The purpose of this study is to determine how students practice the values of PPRA, describe the religious character of students, and analyze the effect of PPRA values on the religious character of students at MAN 3 Padang Pariaman. This research uses a quantitative approach with ex post facto method. The research sample amounted to 99 students from classes X and XI who were selected through proportional random sampling. The data collection instrument was a Likert scale questionnaire, while the data analysis technique used simple linear regression test. The results showed that PPRA values were internalized through real activities such as Bajamba Custom, Student Elections, Friday Blessings, and Ecobricks which fostered religious attitudes, social responsibility, and empathy. The religious character of students is reflected in positive habits such as congregational prayer, daily prayer, Friday donations, and involvement in religious activities. The results of the regression analysis showed a significance value of 0.000 (<0.05) and an R Square value of 0.743, which is